In vitro detection of circulating tumor cells compared by the CytoTrack and CellSearch methods - Hillig, Thore (Tumour Biol, 2015)
Comparison of two methods to detect circulating tumor cells (CTC) CytoTrack and CellSearch through recovery of MCF-7 breast cancer cells, spiked into blood collected from healthy donors. Spiking of a fixed number of EpCAM and pan-cytokeratin positive MCF-7 cells into 7.5 mL donor blood was performed by FACSAria flow sorting. The samples were shipped to either CytoTrack or CellSearch research facilities within 48 h, where evaluation of MCF-7 recovery was performed. CytoTrack and CellSearch analyses were performed simultaneously. Recoveries of MCF-7 single cells, cells in clusters, and clusters were determined. The average numbers of MCF-7 cells/cells in clusters/clusters recovered from blood by the CytoTrack and CellSearch methods were 103 ± 5.9/27 ± 7.9/11 ± 3.5 (95 % CI) and 107 ± 4.4/20 ± 7.1/10 ± 3.5, respectively, with no difference between the two methods (p = 0.37/p = 0.23/p = 0.09). Overall, the recovery of CytoTrack and CellSearch was 68.8 ± 3.9 %/71.1 ± 2.9 %, respectively (p = 0.58). In spite of different methodologies, CytoTrack and CellSearch found similar number of CTCs, when spiking was performed with the EpCAM and pan cytokeratin-positive cell line MCF-7. The results suggest that CytoTrack and CellSearch have similar abilities to identify CTC in vitro.